Flood risk governance in Brazil and the UK: facilitating knowledge exchange through research gaps and the potential of citizen-generated data - Marchezini, Victor; Porto de Albuquerque, Joao; Pitidis, Vangelis; Rudorff, Conrado de Moraes; Lima-Silva, Fernanda; Klonner, Carolin; Martins, Mário Henrique da Mata (Disaster prevention and management, 2022)
Purpose The study aims to identify the gaps and the potentialities of citizen-generated data in four axes of warning system: (1) risk knowledge, (2) flood forecasting and monitoring, (3) risk communication and (4) flood risk governance. Design/methodology/approach Research inputs for this work were gathered during an international virtual dialogue that engaged 40 public servants, practitioners, academics and policymakers from Brazilian and British hazard and risk monitoring agencies during the Covid-19 pandemic. Findings The common challenges identified were lack of local data, data integration systems, data visualisation tools and lack of communication between flood agencies. Originality/value This work instigates an interdisciplinary cross-country collaboration and knowledge exchange, focused on tools, methods and policies used in the Brazil and the UK in an attempt to develop trans-disciplinary innovative ideas and initiatives for informing and enhancing flood risk governance.
Gesehen am 11.08.2022